Net Neutrality: A Fast Lane to Understanding the Trade-offs - Shane Greenstein; Martin Peitz; Tommaso Valletti (University of Mannheim, Department of Economics, 2016)
The "net neutrality" principle has triggered a heated debate and advocates have proposed policy interventions. In this paper, we provide perspective by framing issues in terms of the positive economic factors at work. We stress the incentives of market participants, and highlight the economic conflicts behind the arguments put forward by the different parties. We also identify several key open questions.
urn:nbn:de:bsz:180-madoc-401236
Keywords: L51; L86; 330; Network neutrality; internet; regulation